2021
DOI: 10.4038/jfa.v14i2.5242
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Viral Diseases and Types of Weeds as Alternative Viral Hosts in <em>Dioscorea</em> Fields in Southern Guinea Savannah Agroecology of Nigeria

Abstract: The incidence and severity of viruses infecting yam and weeds were determined on 60 Dioscorea farms in Southern Guinea Savannah Agroecology of Kwara State, North-Central Nigeria. Double Antigen Sandwich Enzyme-Linked Immunosorbent Assay (DAS-ELISA) was used as a serological technique to detect Yam mosaic virus (YMV) and Cucumber mosaic virus (CMV) on Dioscorea and weeds collected from the farms. The survey indicated virus incidence on Dioscorea between 62.8% and 100% and virus severity between 2 and 5 score va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Nevertheless, we found that YMMV can infect several annual weed species that are widespread in yam fields in Guadeloupe and that may play a significant role in the epidemiology of YMMV, considering that Aphis craccivora, an aphid vector of YMMV [48], is polyphagous and could spread YMMV to a wide range of host plants, including yams. Our results add to the previous identification of several weed reservoirs of YMV in yam fields in Nigeria [74,75]. Conventional wisdom holds that the use of pesticides reduces the incidence of viral diseases by negatively affecting vector transmission.…”
Section: Role Of Cropping Practices and Weeds In The Epidemiology Of ...supporting
confidence: 80%
“…Nevertheless, we found that YMMV can infect several annual weed species that are widespread in yam fields in Guadeloupe and that may play a significant role in the epidemiology of YMMV, considering that Aphis craccivora, an aphid vector of YMMV [48], is polyphagous and could spread YMMV to a wide range of host plants, including yams. Our results add to the previous identification of several weed reservoirs of YMV in yam fields in Nigeria [74,75]. Conventional wisdom holds that the use of pesticides reduces the incidence of viral diseases by negatively affecting vector transmission.…”
Section: Role Of Cropping Practices and Weeds In The Epidemiology Of ...supporting
confidence: 80%
“…The possible role of weeds as reservoirs and the impact of farming practices on the epidemiology of yam viruses has not been extensively addressed either [113], although these factors could be significant levers for controlling these viruses through better weed management and/or the use of clean seeds [114,115]. In fact, the sustainable control of yam viruses would be best achieved by combining several approaches, such as frequent seed renewal (using virus-free seed), weed control (mulching, weeding), and/or control of vector populations.…”
Section: Epidemiology: Transmission Reservoir Plants and Cultural Pra...mentioning
confidence: 99%